Impact of COVID pandemic on colorectal cancer - Saimeh, Haitham A. (International Surgery Journal, 2021)
It is highly recommended to set a clear methodology of how physicians should follow up with colorectal cancer patients during the pandemic restrictions. Patients could be followed remotely, for their health condition to be stably monitored.